Approaches to teaching Spanish as a heritage language - Fairclough, Marta (2016)
The purpose of this article is to offer a general view of current pedagogical practices in the teaching of Spanish as a heritage language in the United States, including some of the most innovative practices in the field. After a brief introduction to the socio-demographic and linguistic situation of the Spanish language in that context, the article describes some of the main characteristics of the heritage language learner and summarizes existing pedagogical models and their presence in tertiary institutions. The second part focuses on certain innovative pedagogical practices in the teaching of Spanish as a heritage language. Those innovations are based on the critical language pedagogy model (Fairclough, 1995), whose purpose is to promote language awareness y critical thinking by incorporating into the classroom sociolinguistic content, the acquisition of multiple dialects, translanguaging, cultural ‘multiliteracies’ (New London Group, 1996), and interaction with the community. These innovative practices lead to a stronger connection between the heritage language learner and the speech community, which contributes to the maintenance of the minority language in a linguistic contact situation.